Pengaruh Sosial Ekonomi Keluarga, Pola Asuh Anak, Konsumsi Makanan Terhadap Kecerdasan Anak Balita di TK Santa Bernadeth Kota Manado - Polii, Henny Jeane (Peneliti.net, 2024)
The problems that will be studied are the socio-economic influence of the family, parenting patterns, food consumption on the intelligence of children under five in the Santa Bernadeth Kindergarten, Manado City. This research aims to: 1) Identify; socio-economic characteristics of the family, nutritional knowledge 2) Knowing child rearing patterns, health history 3) Analyzing the influence of nutritional status, health history and intelligence of children under five. This research was conducted on parents of students, especially mothers, totaling 35 people. The data collected consists of primary data and secondary data. Primary data was collected through direct interviews using a questionnaire including family socio-economic status, family income, and parents' formal education level. Family food expenditure, children's health, and parenting patterns. Secondary data was obtained through interviews using a questionnaire. Food consumption was collected quantitatively, namely using the 2 x 24 hour recall method. Data on the child's age, parents' address and general condition of the school. Data measuring the level of nutrition and health knowledge was asked by 13 questions. One question is given a score of 4 if correct and 1 if the answer is incorrect. The total score is converted to 100, so the highest score is 100. If the score is higher, the example answer is better. Nutrition knowledge is classified into: Poor score < 60. Fair 60 – 80, Good > 80. BMI (Body Mass Index) is classified into: Poor 18 – 19.9, Normal 20 – 24.9. Secondary data collected is the general condition of the location study. Data analysis was carried out statistically and descriptively.